Seasonal and Regional Prevalence of Gastrointestinal Parasites in Goats of Samastipur District in Bihar, India - Ram, Pradeep Kumar; Kumar, Pramod; Jha, Amit Kumar; Kumar, Birendra (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study investigated the seasonal and regional prevalence of gastrointestinal parasites in goats across six blocks in Samastipur, Bihar (India). Of 500 fecal samples examined, 74.2% were positive for GIPs. Prevalence was highest during the rainy season (83.05%) and lowest in winter (68.27%). Haemonchus spp. was the most prevalent parasite across all seasons and regions. Prevalence of GIP among different blocks was observed to be highly variable. High prevalence of GIP infection during rainy season might be explained to favorable environmental conditions for growth and development of gastro-intestinal parasite and their stages. Low prevalence during winter season may be attributed to reduced grazing hours of the goats. The findings emphasize the need for seasonal control strategies, particularly during the rainy season.